Effect of Linseed Oil and Fermented Pomegranate Peel Supplementation on the Growth Performance, Digestive Function, and Muscle Fatty Acid Deposition of Heat-Stress Broiler Chickens - Elbaz, Ahmed (Journal of Advanced Veterinary Research, 2023)
This study aimed to investigate the efficiency of adding dietary linseed oil and fermented pomegranate peel on growth performance, digestibility, antioxidant capacity, and muscle fatty acid deposition in heat-stressed broilers. Three hundred Ross 308 broiler chicks (1 day old) were randomly assigned to four groups (group/five replicates). Dietary treatments included: (CON) corn-soybean meal basal diet; (FPP) basal diet + fermented pomegranate peel 4g/kg; (LIO) basal diet + 3% linseed oil; (FPLO) basal diet + fermented pomegranate peel + linseed oil. Compared with CON, broilers fed FPLO diet showed improved body weight gain and feed conversion ratio, while the experimental diet did not affect feed intake. Broilers fed FPP or FPLO diet had higher dressing percentages and lower relative weight of abdominal fat than other groups, whereas other carcass traits and digestive enzymes activities were not influenced by treated groups. Nutrient digestion enhanced, as the crude protein digestibility increased in chickens fed FPP and FPLO, while the crude fat digestibility increased in chickens fed LIO and FPLO. Cholesterol and triglyceride concentrations decreased, while the HDL concentration increased in the chickens fed FPP and FPLO compared to other groups. The oxidative status was enhanced by the experimental additives, as the SOD and GSH-Px levels increased and the MDA level decreased in the serum in treated groups compared to the control group. Chickens fed FPP and FPLO had an improvement in gut health, as the number of Lactobacillus increased and the number of E. coli and Total coliforms decreased. A significant increase in unsaturated fatty acid and a decrease in the n-6:n-3 ratio was noticed in the muscles of chickens fed LIO and FPLO compared to other groups. This research indicates that diets supplemented with a combination of fermented pomegranate peel and linseed oil experience an improvement in growth performance, blood antioxidant capacities, and fatty acid profile in the muscles of heat-stressed broilers.